Ekplorasi dan Alternatif Pertanyaan Matematis Berdasarkan Konteks Masjid Agung Purbalingga - Anton Jaelani; Lukmanul Akhsani (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2023)
Mathematics is an abstract object so students need context to make it easier to learn. The use of context is needed to bring students closer to mathematics, students, teachers, and the context itself. Learning mathematics through an Islamic context is a form of preservation of Islam which is expected to be a means of reminder in daily behavior. The purpose of this study is to explore mathematics and create mathematical questions based on the context of the Great Mosque of Purbalingga. The method of data collection is documentation, observation and library research. Data were analyzed by means of reduction, data presentation, and drawing conclusions. The result is that the Purbalingga Great Mosque building has mathematical elements that students can learn. These are the axis of symmetry, trigonometry, congruence, shape and area of ​​plane figures, comparisons, and measurements. Mathematical questions are also presented to help students develop mathematical adaptation skills to the surrounding situations. Keywords: mathematical exploration, mathematical questions, Purbalingga Great Mosque